Grammatical gender and linguistic complexity, Volume 2 World-wide comparative studies - Di Garbo, Francesca; Olsson, Bruno; Wälchli, Bernhard (Studies in Diversity Linguistics, 2019)
The many facets of grammatical gender remain one of the most fruitful areas of linguistic research, and pose fascinating questions about the origins and development of complexity in language. The present work is a two-volume collection of 13 chapters on the topic of grammatical gender seen through the prism of linguistic complexity. The contributions discuss what counts as complex and/or simple in grammatical gender systems, whether the distribution of gender systems across the world's languages relates to the language ecology and social history of speech communities. Volume two consists of three chapters providing diachronic and typological case studies, followed by a final chapter discussing old and new theoretical and empirical challenges in the study of the dynamics of gender complexity.